"Ambiguous citizens": Kenyan Somalis and the question of belonging. Issue 3 (3rd July 2018) - Scharrer, Tabea
ABSTRACT: This paper deals with the way a "politics of belonging" has been enacted in recent years in Kenya, and what this means for the Somali population of the country. Even though Kenyan Somalis have been treated as "ambiguous citizens" since independence, the question for many of them is not so much if they belong to Kenya, but rather how. In the multi-ethnic state of Kenya, there are other groups as well who are "ambiguous citizens" – including Asians, Whites, Nubians and Arabs – for whom two main dimensions along which "Kenyanness" is constructed come into the foreground: a racial dimension and a cultural dimension. Kenyan Somalis seem to be ambiguous in both of them. Following McIntosh's contention that one way to claim "Kenyanness" is to appeal to "a civic nationalism, in which all groups invested in the nation are equally welcome", this article argues – based on ethnographic data gathered since 2010 as well as archival sources – that many Kenyan Somalis are ready to take this possibility up, if they have the chance to do so.